Consumer Protection Laws in E-Commerce : Legal Gaps and Enforcement Challenges - Djeumenou Jean-Bosco; Alfred Amihere Tit; Joseph Nkoumou (International Forum of Researchers and Lecturers, 2024)
The growth of e-commerce has brought new challenges for consumer protection, with legal frameworks often lagging behind technological advancements. This article analyzes existing consumer protection laws in the e-commerce sector, identifying significant gaps and enforcement issues. Through case studies and regulatory analysis, the paper highlights the challenges of safeguarding consumer rights in a digital marketplace. The study concludes with recommendations for improving legal frameworks to better protect consumers in online transactions.